The protective role of oteuropein against diethylnitrosamine and phenobarbital induced damage in rats - Ozeren, Nurefsan; Kisacam, Mehmet Ali; Kocamuftuoglu, Gonca Ozan; Kaya, Nalan; Ozan, Sema Temizer (Walter de Gruyter Gmbh, 2019)
Objective: Liver cancer is amongst the most lethal cancers worldwide. Diethylnitrosamine (DEN) and phenobarbital (PB) are common agents that form reactive oxygen species (ROS). Oleuropein (OLE) has efficient biological properties and used as a therapeutic agent. In this study, we aimed at investigating OLE against DEN + PB induced liver damage. Methods: Adult Sprague-Dawley rats were divided into 5 groups (n =10): Control, DEN, DEN+ PB, DEN+ PB + OLE and OLE. DEN, DEN+ PB, DEN+ PB+ OLE groups were administered a single dose of 150 mg/kg DEN. After two weeks, DEN+ PB and DEN + PB+ OLE groups received 500 ppm of PB. 10 mg/kg/day of OLE was orally administered to DEN+ PB + OLE and OLE groups. Biochemical and histopathological changes evaluated after the 8 weeks study. Results: DEN and PB application with OLE treatment resulted significant differences, alone or combined. Although there was a significant difference among the groups in terms of liver GSH and MDA levels and CAT activities, there was no significant difference among the groups in SOD activity. In the liver sections of the DEN, DEN + PB and OLE groups, increase in some histopathological findings and TUNEL positive cells were increased compared to the control group. Conclusion: OLE can be used as a protector against the effects of carcinogens causing liver damage.
Keywords: Carcinogen; Rat; Liver; Diethylnitrosamine; Phenobarbital; Oleuropein